1979
DOI: 10.1093/jn/109.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Strain, and Dietary Carbohydrate on the Hepatic Metabolism of Male Rats

Abstract: The effects of age and the duration of feeding either a 65% sucrose or a 65% starch diet to normolipemic Wistar and potentially hyperlipemic-hyperglycemic BHE male rats on hepatic metabolite levels, calculated redox and phosphorylation states were studied. Consistent with previous reports, the feeding of sucrose to BHE rats hastened the appearance of hyperlipemia while having little effect in Wistar rats. The changes in hepatic metabolites were consistent with an increased hepatic lipogenesis in BHE rats. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Sucrose has been shown to increase both plasma cholesterol and TAG concentrations in guinea pigs [27], but a study in rats has demonstrated that substituting sucrose with starch results in a decrease in plasma cholesterol and TAG concentrations [28]. In addition, greater cholesterogenesis in hepatocytes has been observed in rats fed sucrose compared with those fed starch [29].…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose has been shown to increase both plasma cholesterol and TAG concentrations in guinea pigs [27], but a study in rats has demonstrated that substituting sucrose with starch results in a decrease in plasma cholesterol and TAG concentrations [28]. In addition, greater cholesterogenesis in hepatocytes has been observed in rats fed sucrose compared with those fed starch [29].…”
Section: Discussionmentioning
confidence: 99%
“…Age augments these strain differences (4). As BHE rats age, lipemia, glycemia, and a variety of tissue degenerative changes develop (5)(6)(7). One aspect of metabolism heretofore uninvestigated in these two strains is the synthesis of glucose via the gluconeogenic pathway.…”
mentioning
confidence: 99%
“…Triglyceridemia of the fa/fa rats pair-fed on the (S) or (A) diets inversely evolved to that described for ad libitum feeding [3][4][5]17], These authors report a hypertriglyceridemic effect for the sucrose diet compared to starch diet. Changes in our triglyceridemia results can be related to insulinemias.…”
Section: Obesity and Hyperlipemia Evolution O F The Fa/fa Zucker Ratmentioning
confidence: 90%
“…A diet rich in sucrose, as opposed to starch, leads to increased levels of the follow ing parameters in normal subjects and in Wistar and Sprague-Dawley rats: hepatic lip ids [1,2], circulating triacylglycerols [2][3][4][5][6], and insulinemia [5,[7][8][9][10][11] without causing obesity. Glycemia is either changed [5,12,13] or normal [2] after an oral or a venous glucose overload.…”
mentioning
confidence: 99%